Synthesis of N, N-diethyl-2-Hydroxybenzamide Using Methyl Salicylate from Gandapura Oil - Suratmo Suratmo; Rurini Retnowati; Devina Azzuhro (Natural B, Journal of Health and Environmental Sciences, 2013)
The synthesis of N,N-diethyl-2-hydroxybenzamide used methyl salicylate from gandapura oil was conducted. This study aims to find out the synthesis process of N,N-diethyl-2-hydroxybenzamide from methyl salicylate. Methyl salicylate from gandapura oil was mixed with 40% diethylamine solution in diethyl eter and 1% NaOH solution in methanol. The mixture was stirred at 0°C for 1 hour and continued for 24 hours at room temperature. Compound synthesized was separated and determined physical properties include color, shape, odor and melting point, and was identified by FT-IR spectrophotometer and Gas Chromatography-Mass Spectrometer (GC-MS). The results of identification by FT-IR spectrophotometer showed absorption at 1631.67 cm-1 which is the C = O stretching vibrations of amide. The identification results obtained by GC-MS 6 peak. Peak with a retention time of 26.948 minutes with the fragmentation pattern is thought to be the target compound (N, N-diethyl-2-hidroksibenzamida). Identification results from GC-MS obtained 6 peak, and peaks with the retention time of 14.363 minutes showed the presence of methylsalicylate compounds, whereas the peak with a retention time of 26.948 minutes is suspected to be the synthesized compounds (N,N-diethyl-2-hydroxybenzamide). Target compounds synthesized gained by 0.21% in the form of brown solid matter with a melting point of 106-112oC.